Hiring and Training Requirements for Correctional Officers: A Statutory Analysis - Kowalski, Melissa A. (The prison journal, 2020)
U.S. state statutes provide the minimum hiring and training requirements for correctional officers (COs), but it is unclear whether COs have achieved professionalism. This article utilizes a statutory analysis to examine state hiring qualifications and training requirements for COs. The findings reveal that not all 50 have statutes outlining CO hiring and training requirements. Although some states are very specific, many provide only general standards. As such, statutes regarding CO hiring and training are far from uniform.